Inclusion of Ict During the Transformation of the Environment of Learning of the Current with that One in the Centre for the Students – Experience and Attitudes of the Teachers - Mula, Freskina; Mula, Shqipe (European Journal of Multidisciplinary Studies, 2017)
The integration of the technology in education will mean a lot for the basic skills of computerizing and computers programs in a classroom. Effective integration of these technological skills should occur across the curriculum in ways that studies show deepening and enhancing of the learning process. The purpose of this paper addresses the fundamental issue of how schools, teachers and students are ready to use the basic tools of ICT (radio, TV, mobile phones, computers, laptops, projector, application programs, Word, Excel, Power-Point etc. ) during the teaching / learning process, knowing the rapid development of technology. Given the fact that the population in Kosovo consists mainly of new age, youth (age 15-24) who include 55. 3 percent of the population involved in the educational process www. ks-gov. net/esk, then from these data we can draw an image that the use of new technologies by young people and it is necessary installation requirement of ICT in schools, therefore there stems the need for this research. The survey was conducted in five schools of lower secondary education in the municipality of Gjakova/Republic of Kosovo. For conducting this paper there were used these methods: theoretical analysis method, the analysis of pedagogical documentation, the inductive method, comparative and statistical and research instrument was a questionnaire, which is applied to teachers and students. These changes, switching from traditional learning in contemporary learning using the technology undoubtedly help students and enables them to interact theoretical and practical knowledge in order to more easily apply the knowledge acquired.
Keywords: Education, Information and Communication Technology ICT, teaching, learning, teachers, students, classes.